Cellular response of Parachlorella kessleri to a solid surface culture environment - Miyauchi, Hiroki; Ishikawa, Tomoharu; Hirakawa, Yutaro; Sudou, Ayumu; Okada, Katsuhiko; Hijikata, Atsushi; Sato, Norihiro; Tsuzuki, Mikio; Fujiwara, Shoko (Frontiers in Plant Science, 2023)
Attached culture allows high biomass productivity, and is a promising biomass cultivating system because neither a huge facility area nor a large volume of culture medium is needed. This study investigates photosynthetic and transcriptomic behaviors in Parachlorella kessleri cells on a solid-surface after their transfer from liquid culture to elucidate the physiological and gene-expression regulatory mechanisms that underlie their vigorous proliferation. The chlorophyll content shows a decrease at 12 h after the transfer, however, it has fully recovered at 24 h, suggesting temporary decreases in the amounts of light harvesting complexes. On PAM analysis, it is demonstrated that the effective quantum yield of PSII is decreased at 0 h right after the transfer, followed by its recovery in the next 24 h. A similar changing pattern is observed for the photochemical quenching with the PSII maximum quantum yield remaining an almost unaltered level. Non-photochemical quenching was increased at both 0 h and 12 h after the transfer. These observations suggest that electron transfer downstream of PSII but not PSII itself is only temporarily damaged in solid-surface cells just after the transfer, with light energy in excess being dissipated as heat for PSII protection. It thus seems that the photosynthetic machinery acclimates to high-light and/or dehydration stresses through its temporal size-down and functional regulation that start right after the transfer. Meanwhile, transcriptomic analysis by RNA-seq demonstrates temporary upregulation at 12 h after the transfer in many cases, concerning the primary metabolism for CO2 assimilation to amino acid synthesis and photosynthesis, including the above functional regulation, general stress response, and translational machinery necessary for the expression of the proteins. These findings suggest that cells transferred to a solid surface become stressed immediately after the transfer, but can recover their high photosynthetic activity through adaptation of the photosynthetic machinery and metabolic flow as well as induction of general stress response mechanisms within 24 h.